Evaluation of the physical-chemical composition of the fruits of mandacaru (2009)
‘Mandacaru’ (Cereus jamacaru P.) is a native species from the vegetation of the Brazilian North East “Caatinga”, and its fruits could become an important nutritional source for the population of semiarid regions, although it is still not commercially exploited. This work was carried out to evaluate the physical and chemical characteristics of the pulp and peel of ‘mandacaru’ fruit from the Curu Valley, Ceara State, Brazilian North East. ‘Mandacaru’ fruits were harvested and transported to the Embrapa Tropical Agroindustry Laboratory, where approximately 2 Kg of mature and firm fruits were selected for evaluation. These fruits were washed, sanitized and placed under cold storage for future analysis. The fruit pulp and peel were evaluated for: pH, soluble solids (SS), ascorbic acid and total reducing sugars. The experiment was carried out in a completely randomized design, with four replicates. The peel of ‘Mandacaru’ fruit presented pH 4.42, being higher than pulp at pH 4.40. Ascorbic acid content was 100 mg/100g -1 in the pulp, and 80 mg/100g -1 in the peel. A significant difference in SS was detected between pulp and peel, which were 11% and 5%, respectively. On the other hand, fruit pulp presented higher percentage of reducing sugars of 5.76%, as compared to that found in the peel of 1.53%.